Afinidades bióticas entre encinares ibéricos en función de sus taxocenosis de acrídidos (Insecta, Orthoptera). - Presa, J J; Clemente, M E; HERNÁNDEZ, A; García, M D (Boln. Asoc. esp. Ent., 1999)
Orthopterocenosis from eight oak forests of the Iberian Peninsula are analyzed and compared. Two groups of biotopes are stablished: iberian-atlantic and iberian-mediterranean. Carrascal of Font Roja is excluded and reamins isolated, with a very low similarity index value with the other oak forests, because its peculiar characteristics. Use of orthopterocenosis in order to characterize specific biotopes is proposed
Keywords: holm oak forests (PG); orthopterocenosis